(untitled) (Palíndromo, 2020)
The search for lifestyles – an integral part of modernity resulting from modernization – was one of the hallmarks of the globalized modernization process in Brazil. The artist’s figure was of central importance in the daily aestheticization movement that associated current aesthetics with lifestyles. From the transformations that occurred in art during the globalization in Brazil, in the 1950s and 1960s, with the new formulations of Concretism and Neoconcretism — based on the various stages and reinterpretations of European constructivism —, We will see how the press was not only influenced by these trends, but was reshaped and shaped by the hands of the artists. The graphic reform made in Jornal do Brasil by the artist Amilcar de Castro, studied here, is an example of this performance.